Social Media Marketing and Brand Loyalty, The Mediating Role of Brand Trust: a Partial Least Square Algorithm (PLS) Approach - Umar, Fadhil; Raharja, Edy; Mahardika, Jihaddul Akbar; Arkhiansyah, M. Topan Bastari (Universitas Negeri Semarang, 2023)
Purpose: Brand loyalty is a very important aspect along with technological growth, market saturation, globalization, and intense competition. This research seeks to analyze how social media marketing and brand experience impact brand loyalty among students who use XL in Semarang City, with brand trust serving as an intermediary factor.Methods: The research approach is quantitative, with sampling using a purposive sampling technique and the research sample is 133 university students in Semarang. This research establishes a structural equation modeling (SEM) analysis with Smart PLS.Result: The results of this research indicate that both social media marketing and brand experience factors exhibit a favorable and substantial impact on brand loyalty. Moreover, brand trust displays a positive and notable effect on brand loyalty while also acting as a mediator for the positive influence that social media marketing and brand experience have on brand loyalty.Novelty: Analysis and testing of variables that influence user brand loyalty of XL using the Partial Least Square (PLS) algorithm and the Customer Relationship Marketing (CRM) approach. This study examines the telecommunications sector on the advice of previous studies.